Nodulation of Green Chicken (Vigna Radiata L.) With Pupuk P Application on Soil Covered Land (Mucuna Bracteata) - Hasibuan, Jalaluddin Rahmat; Manurung, Saroha; Tarigan, Sri Murti (International Journal on Advanced Science, Education, and Religion, 2023)
Mung bean plants include legume plants whose roots have root nodules which are a symbiosis between the roots and Rhizobium japonicum bacteria. Root nodules function to fix free nitrogen elements, besides that they can also fertilize the soil because they can save the use of NH3 available in the soil and provide nitrogen elements to the soil.Rhizobium is a genus of soil bacteria that are able to symbiotize with plants. There are many types of Rhizobium bacteria, especially in soils with high organic matter content. This study was conducted to determine the compatibility of Rhizobium japonic in mung bean plants (Vigna radiata L) with Rhizobium sp grown on Mucuna bracteata land. To determine the effect of some phosphate fertilizers on the modulation of mung bean (Vigna radiata L.) The results showed that the application of Rhizobium japonicum on mung bean (Vigna radiata L) with Mucuna bracteata land did not show a significantly different adjustment (compatibility) to the height and number of plant leaves. The P0 treatment showed significant differences in the root nodule parameters of the P1, P2 and P3 treatments. Phosphate fertilizer with 50% RP TSP content is the best composition.